Angiotensin converting enzyme (ACE)-peptide interactions: inhibition kinetics, in silico molecular docking and stability study of three novel peptides generated from palm kernel cake proteins - Zarei, Mohammad; Zainal Abidin, Najib; Auwal, Shehu Muhammad; Chay, Shyan Yea; Abdul Haiyee, Zaibunnisa; Md Sikin, Adi; Saari, Nazamid (MDPI, 2019)
Three novel peptide sequences identified from palm kernel cake (PKC) generated protein hydrolysate including YLLLK, WAFS and GVQEGAGHYALL were used for stability study against angiotensin-converting enzyme (ACE), ACE-inhibition kinetics and molecular docking studies. Results showed that the peptides were degraded at different cleavage degrees of 94%, 67% and 97% for YLLLK, WAFS and GVQEGAGHYALL, respectively, after 3 h of incubation with ACE. YLLLK was found to be the least stable (decreased ACE-inhibitory activity) compared to WAFS and GVQEGAGHYALL (increased ACE-inhibitory activity). YLLLK showed the lowest Ki (1.51 mM) in inhibition kinetics study when compared to WAFS and GVQEGAGHYALL with Ki of 2 mM and 3.18 mM, respectively. In addition, ACE revealed the lowest Kappm and Vappmax and higher catalytic efficiency (CE) in the presence of YLLLK at different concentrations, implying that the enzyme catalysis decreased and hence the inhibition mode increased. Furthermore, YLLLK showed the lowest docking score of −8.224 and seven interactions with tACE, while peptide GVQEGAGHYALL showed the higher docking score of −7.006 and five interactions with tACE.